Travel websites: a relevant source of statistical information? - Drozdowska, Marta; Duda-Seifert, Magdalena (Turyzm/Tourism, 2016)
This study explores the two most popular travel websites: TripAdvisor, based fully on the Travel 2.0 and UGC application; and Booking.com, which has developed as an online travel agency website but has also absorbed a modern UGC approach. Their content concerning accommodation in Wrocław was analysed and compared to the official tourist statistics provided by both the Central Statistical Office of Poland, and the Central Register of Hotels and Similar Establishments published by the Ministry of Sport and Tourism. The article aims at an evaluation of the reliability and completeness of the information provided over the internet: firstly from the point of view of a potential customer, secondly for its value for market research purposes. Although electronic word-of-mouth websites are designed both for consumers and suppliers, from a methodological perspective the article is based on a content analysis of tourism social media. The study also contributes to both academic research and the tourism industry by identifying some gaps in existing work and providing an agenda for the future.